2022
DOI: 10.1016/j.jmig.2021.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin to Control Blood Loss during Hysterectomy: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Two RCTs are currently in progress ( ClinicalTrials.gov , NCT04760301 and NCT02911831). A recent meta-analysis by Hafidh et al [ 49 ] showed that prophylactic vasopressin administration reduced intraoperative blood loss compared with normal saline. Hence, future research should explore the clinical utility of intraoperative blood control during hysterectomy in a head-to-head comparison between TXA and other active competitors (e.g., vasopressin).…”
Section: Discussionmentioning
confidence: 99%
“…Two RCTs are currently in progress ( ClinicalTrials.gov , NCT04760301 and NCT02911831). A recent meta-analysis by Hafidh et al [ 49 ] showed that prophylactic vasopressin administration reduced intraoperative blood loss compared with normal saline. Hence, future research should explore the clinical utility of intraoperative blood control during hysterectomy in a head-to-head comparison between TXA and other active competitors (e.g., vasopressin).…”
Section: Discussionmentioning
confidence: 99%
“…For open myomectomy, a combination of uterotonics and peripheral vasoconstrictors is required to effectively reduce blood loss. 63 Minimising intraoperative blood loss during hysterectomy is crucial to reduce perioperative morbidity. The aim of the Hafidh B study was to conduct a systematic review and meta-analysis of seven randomised controlled trials comparing vasopressin and saline for controlling intraoperative blood loss during vaginal and abdominal hysterectomy.…”
mentioning
confidence: 99%
“…However, there was no significant difference between the two groups in terms of mean operative time, mean postoperative haemoglobin change, mean length of hospital stay, incidence of fever, pelvic infections, perioperative blood transfusion, and perioperative complications. 63 According to Ferrari F. et al, the use of an enhanced recovery protocol after gynaecologic surgery leads to a shorter length of stay, regardless of the surgical access and type of gynaecological disease. 31,64 The issue of probes and drains during surgery remains controversial, and the consensus suggests abandoning a routine approach to these procedures.…”
mentioning
confidence: 99%